THE FORMATION OF AN INDEPENDENT CHARACTER IN THE LEARNING PROCESS THROUGH P5 AT SD NEGERI LIALANG - Sayidatul Fariha; Reksa Adya Pribadi; Yoma Hatima (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2026)
This study was motivated by the importance of developing students' independent character through the implementation of the Pancasila Student Profile Strengthening Project (P5). P5 is expected to foster self-control, responsibility, discipline, initiative, and self-confidence in students so that they are able to learn and act independently. The objectives of this study are 1) to describe the process of implementing independent character building through P5 activities, 2) to identify supporting and inhibiting factors, and 3) to determine the independent character values that emerge in fifth-grade students at Lialang Public Elementary School. The method used was a qualitative approach with a descriptive method, using data collection techniques such as observation, interviews, and documentation, including data reduction, data presentation, and conclusion drawing. The results showed that 1) the implementation of P5 at Lialang State Elementary School had been carried out in a planned and systematic manner through project activities such as making relief maps and ice cream stick crafts. These activities encouraged students to work together, be responsible, and complete tasks independently. 2) Supporting factors came from teacher support, a positive learning environment, and active student involvement. Meanwhile, the inhibiting factors included limited time and facilities. 3) This study shows that the implementation of P5 plays an important role in shaping the independent character of students, as indicated by increased discipline, responsibility, self-confidence, and initiative in learning.